Edukasi dan Mitigasi Bencana yang Optimal melalui “Pos Iklim” Desa Pakis Kabupaten Jember - Achmad, Sofyan Maulana; Kartodiprojo, Mikhael Putra; Firmansyah, M. Pramudya; Habibi, M. Wildan; Rahman, Fakhri Fadli; Anggraeni, Ulita Bella; Apriliani, Adhisty Dhea; Rahman, Lubna; Sugiarto, Aditya Dwi; Sagala, Christo Sumurung Tua (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
In terms of Indonesian geography lies in an area that's in the Pacific ring, putting Indonesia in the form of a country with a high threat of disaster. Team of PPK Ormawa IMPA Akasia took issue of breis in jember district pakis as the village historic there was a flood that caused loss of property, objects, to the lives of villagers. The purpose of this devotion is divided into three, namely, young people and rural communities that are conscious and understanding of the urgency of the education of transcanaan, the two create bastions of communities focused on addressing climate adaptation and mitigation, and the third is creating a map of the location of village disaster and a reduced location of vulnerable areas in the village. The method employed is divided into three preparatory, implementation, and supervision processes. The climate post is expected to solve the problems of the existing in the pakis village and can independently develop programs consistent with existing potential in the village to address the optimum climate post with the needs of village people.